Facilities And Sustainability of Tourism Destination Cempaka Park, Cilangkap Cipayung - Pradini, Gagih; Rosdianti, Adella Syahrany; Awaloedin, Dipa Teruna (International Journal of Education, Information Technology, and Others, 2024)
This study describes research on the effect of facility quality on visitor satisfaction and attractiveness in Taman Cempaka Cilangkap Cipayung, East Jakarta. This study adopts qualitative descriptive methods to examine various factors that affect the sustainability of this tourist destination. Through survey, direct observation, and SWOT analysis approaches, the study evaluated visitors' perceptions of the quality of facilities, such as play areas, sports fields, and picnic spots, as well as their relationship to their satisfaction levels. The results showed that the quality of facilities in Taman Cempaka had a positive impact on visitor satisfaction. Factors such as completeness, cleanliness, and condition of the facility received a positive assessment. However, there are some disadvantages to note, such as promotional limitations and lack of innovation in facilities. The recommended development strategy includes increased promotion through digital platforms, collaboration with related parties, and environmental education programs to strengthen the attractiveness of destinations. This research concludes that the management of Taman Cempaka needs to encourage innovation in facility development, as well as improve promotion and marketing strategies to increase the attractiveness and sustainability of the destination. This approach is expected to increase visitor satisfaction and support the long-term sustainability of this tourist destination.